Pengaruh Media Ular Tangga Raksasa Terhadap Kemampuan Penjumlahan dan Pengurangan Anak Hambatan Intelektual di SLB Rela Bhakti 1 Gamping (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to determine the extent to which the giant snakes and ladders game media influences the ability to perform addition and subtraction among students with intellectual disabilities at SLB Rela Bhakti 1 Gamping. This research employed an experimental method with a one-group pre-test and post-test design. The subjects consisted of four second-grade students with mild intellectual disabilities, selected using a saturated sampling technique. Data were collected through mathematics skill tests administered before and after the implementation of learning activities using the giant snakes and ladders media. The data were analyzed using the Wilcoxon Sign Rank Test with SPSS version 27. The results indicated a significant improvement in students’ ability to perform addition and subtraction after learning with the giant snakes and ladders media. The use of this media created a fun learning atmosphere, enhanced students’ focus and participation, and helped them understand mathematical concepts more concretely. Therefore, it can be concluded that the giant snakes and ladders game media has a positive effect on improving the arithmetic skills of students with mild intellectual disabilities, particularly in addition and subtraction operations, and can serve as an interesting and adaptive alternative learning media for students with special needs.